Predictors of spousal coercive control and its association with intimate partner violence evidence from National Family Health Survey-4 (2015-2016) India - Suman Kanougiya; Muthusamy Sivakami; Saurabh Rai (BMC, 2021)
Abstract Background The feminist theory posits that spousal coercive control is not random but a purposeful and systematic men's strategy to control and dominate their female partners. The frequency of coercive control is more than emotional, physical, and sexual intimate partner violence (IPV). Coercive control is usually mistaken with psychological abuse when it is not and has recently gained independent attention within the spectrum of IPV. The role of socioeconomic factors in determining coercive control and associations between coercive control and form of IPV is less researched. Objective We aimed to examine sociodemographic and socioeconomic predictors of spousal coercive control and its association with IPV (past 12-months). Methods We analysed data of 66,013 ever-married women aged 15-49 from the National Family Health Survey (NFHS)-4 (2015-2016). Estimates involved bivariate and multivariate logistic regression models, and marginal effects prediction. Results The prevalence of spousal coercive control is more commonly reported by 48% of women than the prevalence of IPV 25% (emotional 11%, physical 22%, and sexual 5%) in the past 12 months. Adjusted odds ratio indicate that women having three and more children (aOR 1.1, 95% CI: 1.0-1.2), women work status (1.1; 1.1-1.2), husband's secondary (1.1; 1.1-1.2) or higher education (1.1; 1.1-1.2), and husband alcohol consumption (1.7; 1.6-1.7) increase the odds of coercive control. In the fully adjusted model coercive control independently increased the likelihood of experiencing emotional (aOR 2.8.; 95% CI: 2.6, 3.1), physical (2.2; 2.1, 2.3), and sexual (2.5; 2.3, 2.8) IPV in the past 12 months; and with an increase in each additional indicator of coercive control acts, the likelihood of physical, sexual, and emotional IPV further increases. When women reported six indicators of coercive control, the predicted proportion of women experiencing emotional 53%, physical 45%, and sexual IPV was 25% in the fully adjusted model. Conclusion Coercive control limits women's social support and contacts contributing to low self-esteem, self-efficacy, and poor mental health. The purpose of this study is to highlight that understudied coercive control is more common than other forms of IPV and is a potential risk factor for physical, sexual, and emotional IPV independently. The inclusion of coercive control in interventions is crucial to prevent form of IPV. Survivals long-term safety and independence can be secured if the current protection law against domestic violence is extended to encompass coercive control.